Electrode laminate, method for producing same, and electrochemical element
By using an electrode laminate in which a porous metal substrate and an electrode mixture layer are integrated into the electrode of a lithium-ion battery, the problem of increased internal resistance caused by insufficient contact between the electrode and the conductive path is solved, and lower internal resistance and Better electrochemical component performance.
Patent Information
- Application Number
- CN202380045791.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-21
AI Technical Summary
In existing lithium-ion batteries, the contact between the electrode and the conductive path is insufficient, resulting in an increase in internal resistance; although the method of burying the current collector in the electrode can reduce the internal resistance of the electrode, it cannot fully reduce the electrode and the external can and the sealing can. Contact resistance of equal conductivity paths.
The electrode layer of the electrode layer with the electrode coheel layer and the porous metal substrate is used. Contact with the conductivity path.
Through the integration of porous metal substrates and electrode syncloes, the internal resistance of electrochemical elements is significantly reduced, the divergence of the electrode and the conductivity path is improved, and the overall performance of the electrochemical component is enhanced.
Smart Images

Figure CN119343806A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode stack that can be used for assembling an electrochemical device and can reduce internal resistance, a method for producing the same, and an electrochemical device using the electrode stack. Background Art
[0002] In recent years, with the development of portable electronic devices such as mobile phones and notebook computers, and the practical application of electric vehicles, there is a demand for small, lightweight, high-capacity, and high-energy-density batteries.
[0003] At present, in lithium batteries that can meet this requirement, especially lithium ion batteries, the positive electrode active material uses lithium-containing composite oxides such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), the negative electrode active material uses graphite, etc., and an organic electrolyte containing an organic solvent and a lithium salt is used as the non-aqueous electrolyte.
[0004] Furthermore, as the application equipment of lithium ion batteries further develops, lithium ion batteries are required to have a longer life, higher capacity, and higher energy density, and lithium ion batteries that have achieved longer life, higher capacity, and higher energy density are also required to have high reliability.
[0005] However, the organic electrolyte used in lithium-ion batteries contains an organic solvent as a flammable substance, so when the battery is short-circuited or in an abnormal situation, the organic electrolyte may generate abnormal heat. In addition, with the high energy density of lithium-ion batteries in recent years and the increasing trend of the amount of organic solvent in the organic electrolyte, the reliability of lithium-ion batteries is further required.
[0006] Under the above situation, all-solid-state lithium batteries that do not use organic solvents are also being studied. All-solid-state lithium batteries use a molded body of solid electrolytes that do not use organic solvents to replace the conventional organic solvent-based electrolytes. There is no concern about abnormal heat generation from solid electrolytes, and they have high reliability.
[0007] In addition, all-solid-state batteries are not only highly safe, but also highly reliable and environmentally resistant, and have a long lifespan. Therefore, they are expected to be maintenance-free batteries that can contribute to social development and continuously contribute to peace of mind and safety. By providing all-solid-state batteries to society, we can contribute to the achievement of Goal 3 (Ensure healthy lifestyles and promote well-being for all at all ages), Goal 7 (Ensure access to affordable, reliable, sustainable and modern energy for all), Goal 11 (Achieve inclusive, safe, resilient and sustainable cities and human settlements), and Goal 12 (Ensure sustainable production and consumption patterns) among the 17 goals of the Sustainable Development Goals (SDGs) set by the United Nations.
[0008] In addition, batteries such as all-solid-state batteries are known to have flat-shaped batteries such as coin-shaped batteries and button-shaped batteries. In such flat batteries, an outer body formed by interposing a gasket between an outer can and a sealing can and fastening the open end of the outer can inward is used. Moreover, in batteries such as all-solid-state batteries having an electrode (granular electrode) composed of a molded body of an electrode mixture containing an active material, the outer can and the sealing can are usually used as a conductive path from the inside of the battery to the outside, and the granular electrode is contacted with the conductive path, thereby making the outer can and the sealing can function as a pair of electrode terminals, respectively.
[0009] However, when a granular electrode is in contact with the conductive path, the conductive connection between the electrode and the conductive path cannot be sufficiently ensured due to vibration, volume change of the electrode during charge and discharge, etc., and the internal resistance of the battery is likely to increase.
[0010] On the other hand, a technology for reducing the internal resistance in a battery having a conductive path as described above has also been proposed. For example, Patent Document 1 discloses an all-solid-state lithium battery, in which a collector composed of a metal mesh, a foamed metal, etc. is fixed at multiple locations on at least one of a battery housing and a sealing plate of the battery, so that the contact point between the collector and the electrode is movable relative to the battery housing or the sealing plate, and the high elasticity of the collector is utilized to ensure sufficient contact between the collector and the positive and negative electrodes of the battery particles.
[0011] Furthermore, Patent Document 1 discloses, as a method different from the above, an all-solid-state lithium battery in which the current collection efficiency is improved by burying the current collector inside particles of at least one of the positive electrode and the negative electrode, thereby spreading an electron conduction network throughout the electrode. In the all-solid-state lithium battery described in Patent Document 1, the internal resistance can be reduced by these means.
[0012] In addition, Patent Document 2 discloses a flat all-solid-state battery, which can ensure excellent conductivity by arranging a flexible conductive porous component composed of a graphite molded body between a stack of positive electrodes, solid electrolyte layers and negative electrodes and the inner bottom surface of an outer can or an inner bottom surface of a sealing can, thereby maintaining good contact with the electrode stack and the battery container.
[0013] Prior art literature
[0014] Patent Literature
[0015] Patent Document 1: Japanese Patent Application Laid-Open No. 10-247516
[0016] Patent Document 2: International Publication No. 2020 / 066323 Summary of the invention
[0017] Problems to be solved by the invention
[0018] However, as described in Patent Document 1, when the electrode mixture layer is in a movable state and in contact with a current collector composed of a metal mesh or foamed metal with high rigidity, if the force pressing the contact surface is weak, the electrical contact becomes insufficient, and there is a problem of increasing the internal resistance of the battery. In addition, when the current collector is simply buried inside the electrode mixture layer, although the resistance inside the electrode can be reduced by forming a conductive network of the current collector in the electrode, it is not possible to fully reduce the contact resistance between the electrode and the conductive path such as the outer can and the sealing can.
[0019] On the other hand, as described in Patent Document 2, when a porous molded sheet of graphite is arranged between the electrode stack and the battery container, the conductive state between the electrode stack and the battery container can be improved by the pressing pressure of the sheet, but there is room for further research to achieve a better conductive connection including the material of the collector material.
[0020] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an electrode stack that can be used for assembling an electrochemical device and can reduce internal resistance, a method for producing the electrode stack, and an electrochemical device using the electrode stack.
[0021] Methods for solving problems
[0022] The electrode stack of the present invention is characterized in that it has a first electrode, a second electrode and a separation layer between them, at least one of the first electrode and the second electrode has an electrode mixture layer and a sheet-like porous metal substrate, at least a portion of the end of the porous metal substrate including the electrode mixture layer side is buried in the surface portion of the electrode mixture layer and integrated with the electrode mixture layer, and the other end of the porous metal substrate is exposed on the surface of the electrode.
[0023] The electrode stack of the present invention can be manufactured by the manufacturing method of the present invention having the following steps: a first step, placing an electrode mixture into a mold and pressurizing it for pre-forming; a second step, placing a sheet-shaped porous metal substrate on the electrode mixture pre-formed in the first step; and a third step, pressurizing and compressing the porous metal substrate toward the electrode mixture so that at least a portion of the end of the porous metal substrate including the electrode mixture side is buried in the electrode mixture, thereby forming an electrode mixture layer integrated with the porous metal substrate.
[0024] In addition, the electrochemical element of the present invention is characterized in that it has an outer casing and an electrode stack of the present invention sealed inside the outer casing, wherein the outer casing has a conductive path extending from the inside to the outside, so that the porous metal substrate on the electrode surface of the electrode stack is in contact with the conductive path, and the electrode is electrically connected to the conductive path.
[0025] Effects of the Invention
[0026] According to the present invention, it is possible to provide an electrode stack that can be used for assembling an electrochemical device and can reduce internal resistance, a method for producing the electrode stack, and an electrochemical device using the electrode stack. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope photograph of the surface (surface of the electrode) in one example of the electrode laminate of the present invention.
[0028] Figure 2 This is a cross-sectional view schematically showing an example of the electrochemical device of the present invention. DETAILED DESCRIPTION
[0029] The electrode stack of the present invention comprises a first electrode, a second electrode and a separation layer therebetween, wherein at least one of the first electrode and the second electrode comprises an electrode mixture layer and a sheet-like porous metal substrate, wherein at least a portion of the end portion of the porous metal substrate including the electrode mixture layer side is buried in the surface portion of the electrode mixture layer and integrated with the electrode mixture layer, and the other end portion of the porous metal substrate is exposed on the surface of the electrode.
[0030] That is, in the electrode stack of the present invention, at least one of the two electrodes has an electrode mixture layer and a sheet-like porous metal substrate, and the porous metal substrate that functions as a current collector is embedded in the surface portion of the electrode mixture layer in a certain range in the thickness direction from the end (end face) on the electrode mixture layer side. Therefore, by maintaining the electrode mixture constituting the electrode mixture layer in at least a portion of the pores in the porous metal substrate, the porous metal substrate and the electrode mixture layer are integrated, thereby, the conductivity between the electrode mixture layer and the current collector becomes very good.
[0031] In addition, in the electrode stack of the present invention, in the electrode having an electrode mixture layer and a sheet-like porous metal substrate, the end (end face) of the porous metal substrate on the side opposite to the electrode mixture layer is exposed on the surface (surface of the electrode). Therefore, when an outer casing having a conductive path from the inside to the outside is used and the electrode stack of the present invention is accommodated inside the outer casing to form an electrochemical element, the conductivity between the electrode and the conductive path is also very good by making the porous metal substrate on the surface of the electrode contact with the conductive path.
[0032] By such action, the electrode stack of the present invention can reduce the internal resistance of the electrochemical element and improve its characteristics. That is, the electrochemical element of the present invention having the electrode stack of the present invention has low internal resistance and excellent characteristics due to the above action of the electrode stack.
[0033] It should be noted that in the electrode stack of the present invention, any one of the first electrode and the second electrode has the above-mentioned structure, that is, it has an electrode mixture layer and a sheet-like porous metal substrate, at least a portion of the end of the porous metal substrate including the electrode mixture layer side is embedded in the surface layer of the electrode mixture layer and integrated with the electrode mixture layer, and the other end of the porous metal substrate is exposed on the surface of the electrode, thereby reducing the internal resistance of the electrochemical element. However, from the perspective of further reducing the internal resistance and forming an electrochemical element with better characteristics, it is preferred that both the first electrode and the second electrode have the above-mentioned structure.
[0034] It should be noted that the electrochemical element of the present invention includes batteries, capacitors, etc. In addition, when the electrochemical element of the present invention is a battery, it includes a primary battery and a secondary battery, and in addition, it includes a battery (all-solid-state battery) having a solid electrolyte layer between the positive electrode and the negative electrode, and a battery (battery other than all-solid-state battery) having a separator between the positive electrode and the negative electrode and an electrolyte (non-aqueous electrolyte, aqueous electrolyte, and gel electrolyte obtained by gelling these electrolytes) containing a solvent. Furthermore, when the electrochemical element of the present invention is a capacitor, it includes a double-layer capacitor, a lithium ion capacitor, etc.
[0035] <Electrode Laminate>
[0036] The electrode stack includes a first electrode, a second electrode, and a separator interposed therebetween.
[0037] When the electrochemical element using the electrode stack is a battery or a lithium ion capacitor, one of the first electrode and the second electrode is a positive electrode and the other is a negative electrode. In addition, when the electrochemical element using the electrode stack is a double electric layer capacitor, the first electrode and the second electrode can use electrodes of the same structure.
[0038] Moreover, as described above, at least one of the first electrode and the second electrode has the following structure: it has an electrode mixture layer and a sheet-shaped porous metal substrate, at least a portion of the end portion of the porous metal substrate including the electrode mixture layer side is buried in the surface portion of the electrode mixture layer and integrated with the electrode mixture layer, and the other end portion of the porous metal substrate is exposed on the surface of the electrode.
[0039] In the electrode laminate used in the battery, when the electrode having the above-mentioned structure is a positive electrode, the electrode mixture layer is composed of a positive electrode mixture containing a positive electrode active material and the like.
[0040] When the electrode having the above-mentioned structure is the positive electrode of a primary battery, the positive electrode active material can use the same material as the positive electrode active material used in the non-aqueous electrolyte primary battery, alkaline battery, manganese battery, etc. known in the past. Specifically, for example, manganese dioxide, lithium-containing manganese oxides [for example, LiMn3O6, composite oxides having the same crystal structure as manganese dioxide (β-type, γ-type, or a structure in which β-type and γ-type are mixed, etc.) and a Li content of 3.5% by mass or less, preferably 2% by mass or less, more preferably 1.5% by mass or less, and particularly preferably 1% by mass or less, etc.], Li a Ti 5 / 3 Lithium-containing composite oxides such as O4 (4 / 3≤a<7 / 3); vanadium oxides; niobium oxides; titanium oxides; sulfides such as iron disulfide; graphite fluoride; silver sulfides such as Ag2S; nickel oxides such as NiO2, etc.
[0041] When the electrode having the above structure is used as a positive electrode of a secondary battery, the positive electrode active material may be the same as the positive electrode active material used in conventionally known non-aqueous electrolyte secondary batteries, alkaline secondary batteries, etc. Specifically, Li 1-x M r Mn 2-r O4 (wherein M is at least one element selected from the group consisting of Li, Na, K, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Zr, Fe, Co, Ni, Cu, Zn, Al, Sn, Sb, In, Nb, Ta, Mo, W, Y, Ru and Rh, 0≤x≤1, 0≤r≤1) represented by a spinel lithium manganese composite oxide, Li r Mn (1-s-t) Ni s M tO (2-u) F v (where M is at least one element selected from the group consisting of Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr, and W, 0 ≤ r ≤ 1.2, 0 < s < 0.5, 0 ≤ t ≤ 0.5, u + v < 1, -0.1 ≤ u ≤ 0.2, 0 ≤ v ≤ 0.1) The layered compound represented, Li 1-x Co 1-r M r O2 (where M is at least one element selected from the group consisting of Al, Mg, Ti, V, Cr, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, and Ba, 0 ≤ x ≤ 1, 0 ≤ r ≤ 0.5) The lithium cobalt composite oxide represented, Li 1-x Ni 1-r M r O2 (where M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, and Ba, 0 ≤ x ≤ 1, 0 ≤ r ≤ 0.5) The lithium nickel composite oxide represented, Li 1+s-x M 1-r N r PO4F s (where M is at least one element selected from the group consisting of Fe, Mn, and Co, N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V, and Ba, 0 ≤ x ≤ 1, 0 ≤ r ≤ 0.5, 0 ≤ s ≤ 1) The olivine-type composite oxide represented, Li 2-x M 1-r N r P2O7 (where M is at least one element selected from the group consisting of Fe, Mn, and Co, N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V, and Ba, 0 ≤ x ≤ 2, 0 ≤ r ≤ 0.5) The pyrophosphate compound shown, nickel hydroxide, silver oxide, etc. can be used alone, or two or more of them can be used in combination.
[0042] In the case where the electrochemical element is an all-solid-state secondary battery, the average particle size of the positive electrode active material is preferably 1 μm or more, more preferably 2 μm or more, and preferably 10 μm or less, more preferably 8 μm or less. It should be noted that the positive electrode active material can be a primary particle or a secondary particle formed by agglomeration of primary particles. If a positive electrode active material having an average particle size in the above range is used, the interface with the solid electrolyte contained in the positive electrode increases, so the output characteristics of the battery are further improved.
[0043] The average particle size of various particles (positive electrode active material, solid electrolyte, etc.) referred to in this specification refers to the value (D) at which the cumulative fraction based on volume reaches 50% diameter when the integrated volume is calculated from particles with small particle size using a particle size distribution measuring device (Microtrac particle size distribution measuring device "HRA9320" manufactured by Nikkiso Co., Ltd., etc.). 50 ).
[0044] When the electrochemical device is an all-solid-state secondary battery, the positive electrode active material preferably has a reaction inhibition layer on its surface for inhibiting the reaction with the solid electrolyte contained in the positive electrode.
[0045] In the electrode mixture layer (positive electrode mixture layer), if the positive electrode active material is in direct contact with the solid electrolyte, the solid electrolyte is oxidized to form a resistance layer, and the ion conductivity in the electrode mixture layer may be reduced. By providing a reaction inhibition layer that inhibits the reaction with the solid electrolyte on the surface of the positive electrode active material, the positive electrode active material is prevented from directly contacting the solid electrolyte, thereby suppressing the reduction of ion conductivity in the electrode mixture layer caused by oxidation of the solid electrolyte.
[0046] The reaction inhibition layer can be made of a material having ion conductivity and capable of inhibiting the reaction of the positive electrode active material with the solid electrolyte. As materials capable of constituting the reaction inhibition layer, for example, oxides containing Li and at least one element selected from the group consisting of Nb, P, B, Si, Ge, Ti and Zr can be cited, and more specifically, Nb-containing oxides such as LiNbO3, Li3PO4, Li3BO3, Li4SiO4, Li4GeO4, LiTiO3, LiZrO3, Li2WO4, etc. can be cited. The reaction inhibition layer can contain only one of these oxides, or more than two, and further, a plurality of these oxides can also form a composite compound. Among these oxides, Nb-containing oxides are preferably used, and LiNbO3 is more preferably used.
[0047] The reaction suppression layer is preferably present on the surface in an amount of 0.1 to 1.0 parts by mass relative to 100 parts by mass of the positive electrode active material. Within this range, the reaction between the positive electrode active material and the solid electrolyte can be suppressed well.
[0048] Examples of a method for forming a reaction inhibition layer on the surface of a positive electrode active material include a sol-gel method, a mechanofusion method, a CVD method, a PVD method, and an ALD method.
[0049] From the viewpoint of further increasing the energy density of the electrochemical device, the content of the positive electrode active material in the positive electrode mixture is preferably 60 to 85% by mass.
[0050] The positive electrode mixture can contain a conductive aid. As a specific example, carbon materials such as graphite (natural graphite, artificial graphite), graphene, carbon black, carbon nanofibers, and carbon nanotubes can be listed. It should be noted that, for example, when Ag2S is used as the active material, Ag with conductivity is generated during the discharge reaction, so it is also possible not to contain a conductive aid. In the case of containing a conductive aid in the positive electrode mixture, its content is preferably more than 1.0 parts by mass when the content of the positive electrode active material is set to 100 parts by mass, preferably less than 7.0 parts by mass, and more preferably less than 6.5 parts by mass.
[0051] In addition, the positive electrode mixture can contain a binder. As a specific example, fluororesins such as polyvinylidene fluoride (PVDF) can be cited. It should be noted that, for example, in the case where a sulfide-based solid electrolyte is contained in the positive electrode mixture (details are described later), even if a binder is not used, when good formability can be ensured when forming an electrode mixture layer (positive electrode mixture layer), the positive electrode mixture may not contain a binder.
[0052] In the positive electrode mixture, when a binder is required, its content is preferably 15% by mass or less, and preferably 0.5% by mass or more. On the other hand, in the positive electrode mixture, when formability can be obtained even without a binder, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and further preferably 0% by mass (i.e., without a binder).
[0053] When the electrochemical device is an all-solid-state battery (all-solid-state primary battery, all-solid-state secondary battery), it is preferred that a solid electrolyte be contained in the positive electrode mixture.
[0054] The solid electrolyte contained in the positive electrode mixture is not particularly limited as long as it has lithium ion conductivity, and for example, a sulfide-based solid electrolyte, a hydride-based solid electrolyte, a halide-based solid electrolyte, an oxide-based solid electrolyte, etc. can be used.
[0055] As sulfide-based solid electrolytes, particles such as Li2S-P2S5, Li2S-SiS2, Li2S-P2S5-GeS2, and Li2S-B2S3 glass can be cited. In addition, thio-LISICON-type sulfide-based solid electrolytes [Li10 GeP2S 12 、Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 etc. such as those represented by the general formula Li 12-12a-b+c+6d-e M 1 3+a-b-c-d M 2 b M 3 c M 4 d M 5 12-e X e (where M 1 is Si, Ge or Sn, M 2 is P or V, M 3 is Al, Ga, Y or Sb, M 4 is Zn, Ca or Ba, M 5 is S, or S and O, X is F, Cl, Br or I, 0 ≤ a < 3, 0 ≤ b + c + d ≤ 3, 0 ≤ e ≤ 3) solid state electrolytes), sulfide-based solid state electrolytes with a thio-LISICON crystal structure shown by examples below.
[0056] As hydride-based solid state electrolytes, for example, LiBH4, solid solutions of LiBH4 and the following alkali metal compounds (e.g., solid solutions with a molar ratio of LiBH4 to alkali metal compounds of 1:1 to 20:1), etc. can be cited. As the alkali metal compounds in the solid solutions, at least one selected from the group consisting of lithium halides (LiI, LiBr, LiF, LiCl, etc.), rubidium halides (RbI, RbBr, RbF, RbCl, etc.), cesium halides (CsI, CsBr, CsF, CsCl, etc.), lithium amide, rubidium amide, and cesium amide can be cited.
[0057] As halide-based solid state electrolytes, for example, monoclinic LiAlCl4, defective spinel-type or layered LiInBr4, monoclinic Li 6-3m Y m X6 (where 0 < m < 2 and X = Cl or Br), etc. In addition, known substances described in, for example, International Publication No. 2020 / 070958 and International Publication No. 2020 / 070955 can be used.
[0058] As oxide-based solid state electrolytes, for example, garnet-type Li7La3Zr2O 12 、NASICON-type Li 1+ O Al 1+O Ti2-O (PO4)3、Li 1+p Al 1+p Ge 2-p (PO4)3, Perovskite-type Li 3q La 2 / 3-q TiO3, etc.
[0059] Among these solid electrolytes, sulfide-based solid electrolytes are preferred from the perspective of high lithium ion conductivity, and sulfide-based solid electrolytes containing Li and P are more preferred. From the perspective of higher lithium ion conductivity and high chemical stability, sulfide-based solid electrolytes having an argyrodite-type crystal structure are further preferred.
[0060] As a sulfide-based solid electrolyte having an argyrodite-type crystal structure, a substance represented by the following general composition formula (1) or the following general composition formula (2), such as Li6PS5Cl, is particularly preferred.
[0061] Li 7-x+y PS 6-x Cl x+y (1)
[0062] In the above general composition formula (1), 0.05≤y≤0.9, -3.0x+1.8≤y≤-3.0x+5.7.
[0063] Li 7-a PS 6-a Cl b Br c (2)
[0064] In the above general composition formula (2), a=b+c, 0 <a≤1.8,0.1≤b / c≤10.0。
[0065] From the viewpoint of reducing grain boundary resistance, the average particle size of the solid electrolyte is preferably greater than 0.1 μm, more preferably greater than 0.2 μm. On the other hand, from the viewpoint of forming a sufficient contact interface between the active material and the solid electrolyte, it is preferably less than 10 μm, more preferably less than 5 μm.
[0066] From the viewpoint of further improving the ionic conductivity in the positive electrode and further improving the output characteristics of the electrochemical element, when the content of the positive electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the positive electrode mixture is preferably 10 parts by mass or more, more preferably 15 parts by mass or more. However, when the amount of the solid electrolyte in the positive electrode mixture is too much, the amount of other components decreases, and the effect brought by them is likely to become smaller. Therefore, when the content of the positive electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the positive electrode mixture is preferably 65 parts by mass or less, more preferably 60 parts by mass or less.
[0067] In the electrode laminate used in the battery, when the electrode having the above-mentioned structure is a negative electrode, the electrode mixture layer is composed of a negative electrode mixture containing a negative electrode active material and the like.
[0068] As the negative electrode active material, for example, carbon materials such as graphite, lithium titanium oxide (lithium titanate, etc.), simple substances containing elements such as Si and Sn, compounds (oxides, etc.) and alloys thereof, etc. In addition, lithium metal and lithium alloys (lithium-aluminum alloys, lithium-indium alloys, etc.) can also be used as negative electrode active materials.
[0069] From the viewpoint of further increasing the energy density of the battery, the content of the negative electrode active material in the negative electrode mixture is preferably 40 to 80% by mass.
[0070] The negative electrode mixture may contain a conductive aid. Specific examples thereof include the same conductive aids as those previously exemplified as the materials that may be contained in the positive electrode mixture. When the content of the negative electrode active material is set to 100 parts by mass, the content of the conductive aid in the negative electrode mixture is preferably 10 to 30 parts by mass.
[0071] In addition, the negative electrode mixture can contain a binder. As a specific example, the same substance as the binder previously exemplified as a substance that can be contained in the positive electrode mixture can be cited. It should be noted that, for example, as in the case where a sulfide-based solid electrolyte is contained in the negative electrode mixture (described later), even if a binder is not used, when good formability can be ensured when forming the electrode mixture layer (negative electrode mixture layer), the negative electrode mixture may not contain a binder.
[0072] In the negative electrode mixture, when a binder is required, its content is preferably 15% by mass or less, and preferably 0.5% by mass or more. On the other hand, in the negative electrode mixture, when formability can be obtained even without a binder, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and further preferably 0% by mass (i.e., without a binder).
[0073] In the case where the electrochemical element is an all-solid-state battery, it is preferred that the negative electrode mixture contain a solid electrolyte. As a specific example, the same substance as the solid electrolyte previously exemplified as a substance that can be contained in the positive electrode mixture can be cited. Among the solid electrolytes exemplified above, from the perspective of high lithium ion conductivity and the function of improving the formability of the negative electrode mixture, it is preferred to use a sulfide-based solid electrolyte, more preferably a sulfide-based solid electrolyte having a argyrodite-type crystal structure, and further preferably a solid electrolyte represented by the above-mentioned composition formula (1) or the above-mentioned composition formula (2).
[0074] For the same reasons as in the case of the positive electrode mixture, the average particle size of the solid electrolyte in the negative electrode mixture is preferably 0.1 μm or more, more preferably 0.2 μm or more, and is preferably 10 μm or less, more preferably 5 μm or less.
[0075] From the viewpoint of further improving the ionic conductivity in the negative electrode and further improving the output characteristics of the electrochemical element, when the content of the negative electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the negative electrode mixture is preferably 30 parts by mass or more, more preferably 35 parts by mass or more. However, when the amount of the solid electrolyte in the negative electrode mixture is too much, the amount of other components decreases, and the effect brought by them may become smaller. Therefore, when the content of the negative electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the negative electrode mixture is preferably 130 parts by mass or less, more preferably 110 parts by mass or less.
[0076] When the electrochemical device using the electrode stack is an electric double layer capacitor, the electrode mixture layer in the electrode having the above-mentioned structure can be formed of an electrode mixture having the same structure as the above-mentioned positive electrode mixture except that activated carbon is used as the active material.
[0077] In addition, when the electrochemical element using the electrode stack is a lithium ion capacitor, the electrode mixture layer in the electrode having the above-mentioned structure can be formed by an electrode mixture of the same structure as the electrode mixture in the above-mentioned electrode of the double-layer capacitor when the electrode is a positive electrode, and can be formed by an electrode mixture of the same structure as the above-mentioned negative electrode mixture when the electrode is a negative electrode.
[0078] In the electrode having the above-mentioned structure, the porous metal substrate preferably uses a foamed metal porous body. As a specific example of the foamed metal porous body, "Celmet (registered trademark)" of Sumitomo Electric Industries, Ltd. can be cited. It should be noted that such a porous metal substrate is usually compressed and the thickness is reduced when the electrode is made together with the electrode mixture, so the thickness before being used for the electrode (electrode stack) is thicker than the above-mentioned thickness (thickness in the electrode). For example, the thickness of the porous metal substrate before compression is preferably more than 0.1mm, more preferably more than 0.3mm, particularly preferably more than 0.5mm, on the other hand, preferably less than 3mm, more preferably less than 2mm, and particularly preferably less than 1.5mm. During the manufacture of the electrode stack described later, the porous metal substrate is compressed in the thickness direction, and its thickness becomes the value described later.
[0079] In order to make it easy to fill the electrode mixture into the pores of the porous metal substrate and to easily integrate the porous metal substrate and the electrode mixture layer in the process of pressurizing the porous metal substrate and the electrode mixture, the porosity of the porous metal substrate before compression is preferably 80% or more, more preferably 90% or more, and particularly preferably 95% or more. On the other hand, in order to increase the amount of the substrate to a certain extent and improve the conductivity, the porosity is preferably 99.5% or less, more preferably 99% or less, and particularly preferably 98.5% or less.
[0080] In the case where only either the first electrode or the second electrode in the above-mentioned electrode stack is an electrode having the above-mentioned structure, the other electrode can be, for example, a molded body of an electrode mixture [an electrode composed only of (particles, etc.), an electrode having a structure in which a molded body of an electrode mixture (electrode mixture layer) is formed on a current collector (a current collector other than a porous metal substrate such as a metal foil)], a lithium sheet, a lithium alloy sheet, or other metal sheet functioning as a negative electrode active material (in the case where the electrochemical element is a battery and the electrode is its negative electrode), etc.
[0081] In the electrode constructed as described above, from the viewpoint of more reliably integrating the porous metal substrate and the electrode mixture layer, the thickness of the portion of the porous metal substrate buried in the electrode mixture layer is preferably greater than 10% of the thickness of the porous metal substrate (the thickness of the entire porous metal substrate, including the thickness of the portion coexisting with the electrode mixture layer. Unless otherwise specified, the thickness of the porous metal substrate shall apply the same below), and more preferably greater than 20%.
[0082] In the electrode of the above-mentioned structure, in order to reduce the resistance when contacting with the conductive path in the outer body of the electrochemical element, it is preferred that the end of the porous metal substrate on the opposite side of the electrode mixture layer side (hereinafter sometimes referred to as the surface side end) is not embedded in the electrode mixture layer, and the end of the electrode (the surface of the electrode) is only composed of the porous metal substrate. That is, when the porous metal substrate is compressed in the thickness direction when manufacturing the electrode stack described later, the pores at the surface side end of the porous metal substrate are flattened and disappear, and it is preferred that only the porous metal substrate is exposed on the electrode surface. However, a part of the pores at the surface side end of the porous metal substrate may not be flattened and still remain as pores, or become a state filled with an electrode mixture therein, and a part of the electrode mixture may also be exposed on the surface of the electrode together with the surface side end of the porous metal substrate without causing a large impact on the contact resistance with the conductive path. That is, as long as the surface side end of the porous metal substrate can be exposed on the electrode surface, the entire porous metal substrate (100% of the thickness of the porous metal substrate) can also be buried in the surface layer of the electrode mixture layer. By filling the electrode mixture into the pores of the porous metal substrate until it reaches the surface of the electrode, the integration of the electrode mixture and the porous metal substrate can be made more reliable.
[0083] Figure 1 A scanning electron microscope (SEM) photograph of the surface of an example of the electrode stack of the present invention is shown in FIG. Figure 1 The surface of the electrode stack shown (the surface of the electrode) has the end of the porous metal substrate 10 of the electrode having the above-mentioned structure of the electrode stack exposed, and a part of the electrode mixture 11 is also exposed on the surface of the electrode by entering the pores existing at the end of the porous metal substrate.
[0084] However, the greater the proportion (area ratio) of the electrode mixture exposed on the surface of the electrode, the greater the contact resistance between the porous metal substrate and the conductive path of the electrochemical element. Therefore, the area ratio of the electrode mixture exposed on the electrode surface is preferably less than 50% when viewed from above, more preferably less than 25%, further preferably less than 15%, and particularly preferably less than 10%.
[0085] In the electrode of the above-mentioned structure, when at least a part of the porous metal substrate is buried in the surface part of the electrode mixture layer, from the viewpoint of more reliably integrating the porous metal substrate and the electrode mixture layer, the thickness of the porous metal substrate is preferably 1% or more of the overall thickness of the electrode mixture layer (including the thickness of the part coexisting with the porous metal substrate. The "thickness of the electrode mixture layer" mentioned below, unless otherwise specified, refers to the "overall thickness of the electrode mixture layer" mentioned here), more preferably 2% or more, and particularly preferably 3% or more. In addition, from the viewpoint of improving the filling property of the electrode mixture layer in the electrode, the thickness of the porous metal substrate is preferably less than 30% of the thickness of the electrode mixture layer, more preferably less than 20%, and particularly preferably less than 10%.
[0086] It should be noted that, in the electrode of the above-mentioned structure, the thickness of the porous metal substrate is preferably 10 μm or more, more preferably 20 μm or more, and particularly preferably 30 μm or more, and on the other hand, it is preferably 300 μm or less, more preferably 200 μm or less, and particularly preferably 100 μm or less. In addition, the thickness of the electrode mixture layer is preferably 0.2 mm or more, more preferably 0.5 mm or more, and particularly preferably 0.7 mm or more, and on the other hand, it is preferably 2 mm or less, more preferably 1.7 mm or less, and particularly preferably 1.5 mm or less.
[0087] The thickness of the porous metal substrate and the thickness of the electrode mixture layer in the electrode stack are obtained by observing the cross section of the electrode in the thickness direction using SEM at a magnification of 50 to 1000 times, respectively, and the maximum value of the width in the thickness direction of the area where the porous metal substrate can be confirmed and the area where the electrode mixture can be confirmed. In addition, the thickness of the portion of the porous metal substrate buried in the electrode mixture layer is obtained by the maximum value of the width in the thickness direction of the portion where the area where the porous metal substrate can be confirmed overlaps with the area where the electrode mixture can be confirmed (the values in the embodiments described below are obtained by these methods).
[0088] In addition, the proportion of the electrode mixture exposed on the surface of the electrode (area ratio) is calculated by the ratio (A / B) of the sum of the areas of the portions where the electrode mixture is exposed: A, and the area of the entire electrode: B, in an image obtained by observing the surface of the electrode at a magnification of 50 to 200 times using a SEM (the values in the examples described below are calculated using this method).
[0089] In the electrode stack, a separator is interposed between the first electrode and the second electrode, and in batteries and capacitors that do not use an electrolyte containing a solvent, such as an all-solid-state battery, a solid electrolyte layer is used as the separator.
[0090] As a specific example of the solid electrolyte constituting the solid electrolyte layer, the same substances as those previously exemplified as substances that can be contained in the positive electrode mixture can be cited. Among the solid electrolytes exemplified above, it is preferred to use a sulfide-based solid electrolyte, more preferably a sulfide-based solid electrolyte having an argyrodite-type crystal structure, and further preferably a solid electrolyte represented by the above-mentioned composition formula (1) or the above-mentioned composition formula (2) from the perspective of high lithium ion conductivity and the function of improving the moldability of the negative electrode mixture.
[0091] The solid electrolyte layer may have a porous body such as a resin nonwoven fabric as a support.
[0092] The thickness of the solid electrolyte layer is preferably 10 to 200 μm.
[0093] In an electrode stack used in a battery or capacitor using an electrolyte containing a solvent, a separator is used as a separation layer interposed between a first electrode and a second electrode.
[0094] The separator is preferably one that has sufficient strength and can retain a large amount of electrolyte. From this viewpoint, a microporous film or nonwoven fabric made of polyethylene, polypropylene or ethylene-propylene copolymer having a thickness of 10 to 50 μm and an opening ratio of 30 to 70% is preferred.
[0095] The electrode stack can be produced by a production method including the following first to third steps.
[0096] In the first step, the electrode mixture is put into a mold and pressurized to perform pre-molding. The surface pressure of the pre-molding in the first step is preferably 30 to 500 MPa, for example.
[0097] In the following second step, a porous metal substrate is placed on the electrode mixture preformed in the first step, and in the following third step, the porous metal substrate is pressurized and compressed against the electrode mixture. By pressurizing in the third step, at least a portion of the end of the porous metal substrate including the electrode mixture side is buried in the electrode mixture, forming an electrode mixture layer integrated with the porous metal substrate.
[0098] As described above, in the third step, the porous metal substrate is compressed in the thickness direction, and as the degree of compression, from the viewpoint of more reliably forming the porous metal substrate and the electrode mixture layer, the thickness of the porous metal substrate after compression is preferably set to 30% or less of the thickness before compression, more preferably to 20% or less, and particularly preferably to 10% or less. In addition, from the viewpoint of maintaining a certain degree of electrode mixture in the voids of the porous metal substrate and improving the bonding strength between the porous metal substrate and the electrode mixture layer, the thickness of the porous metal substrate after compression in the third step is preferably set to 1% or more of the thickness before compression, and more preferably to 2% or more.
[0099] In order to compress and mold the electrode mixture and fully improve the density of the electrode mixture layer, the surface pressure during the pressurization in the third process is preferably 800MPa or more, more preferably 1000MPa or more, and particularly preferably 1200MPa or more. The upper limit of the surface pressure during the pressurization in the third process is not particularly specified, and in a commonly used pressurizing device, usually about 2000MPa is the upper limit.
[0100] By going through the first step to the third step, an electrode having the following structure can be obtained: at least a portion of the end of the porous metal substrate including the electrode mixture layer side (a certain range in the thickness direction from the end of the porous metal substrate) is buried in the surface portion of the electrode mixture layer and integrated with the electrode mixture layer, and the other end of the porous metal substrate is exposed on the surface of the electrode.
[0101] It should be noted that if the surface pressure during pressurization in the third step increases, cracks may occur when the porous metal substrate is compressed. However, even if it is cut and fragmented, as long as its end is exposed on the surface of the electrode, it can help reduce the contact resistance.
[0102] In the case of manufacturing an electrode stack with a separator, two electrodes obtained as described above are prepared and arranged on both sides of the separator to form an electrode stack. In addition, the electrode arranged on one side of the separator can be set as an electrode other than the electrode of the above-mentioned structure (an electrode composed of a molded body of an electrode mixture without a current collector, an electrode using a metal foil or the like as a current collector, etc.).
[0103] In the case of manufacturing an electrode stack with a solid electrolyte layer, two electrodes obtained as described above are prepared, and they are arranged on both sides of the solid electrolyte layer, and pressurized as needed to form an electrode stack. In addition, the electrode arranged on one side of the solid electrolyte layer can also be set to an electrode other than the electrode of the above-mentioned structure (an electrode consisting of a molded body of an electrode mixture without a collector, an electrode using a metal foil, etc. for the collector, etc.).
[0104] Furthermore, when manufacturing an electrode stack having a solid electrolyte layer, a preparatory step of placing the solid electrolyte into a mold and pressurizing it for preforming can be provided before the first step, in which the electrode mixture is placed on the preformed solid electrolyte and then the first step is implemented.
[0105] The surface pressure during preforming in the preliminary step is preferably, for example, 30 to 120 MPa.
[0106] In addition, it is also possible to manufacture an electrode stack having electrodes of the above-mentioned structure on both sides of the solid electrolyte layer by further sequentially performing the first step, the second step, and the third step on the other side of the solid electrolyte layer having the electrodes of the above-mentioned structure formed on one side through the first step, the second step, and the third step from the preparatory step.
[0107] <Electrochemical Components>
[0108] The electrochemical element of the present invention comprises an outer casing and an electrode stack of the present invention sealed inside the outer casing, wherein the outer casing has a conductive path extending from the inside of the outer casing to the outside, so that the porous metal substrate on the electrode surface of the electrode stack is in contact with the conductive path, and the electrode is electrically connected to the conductive path.
[0109] Figure 2 A cross-sectional view schematically showing an example of the electrochemical device of the present invention is shown in FIG. Figure 2 In the electrochemical element 100 shown, an electrode stack 140 having a first electrode 110, a second electrode 120, and a separator 130 interposed therebetween is enclosed in an outer casing formed of a metal outer can 150, a metal sealing can 160, and a resin gasket 170 interposed therebetween. The sealing can 160 is fitted into the opening of the outer can 150 via the gasket 170, and the opening end of the outer can 150 is tightened inwardly, whereby the gasket 170 abuts against the sealing can 160, thereby sealing the opening of the outer can 150 and forming a sealed structure inside the element.
[0110] When the electrode stack 140 has a solid electrolyte layer as the separator 130, for example, only the electrode stack 140 is sealed in the outer casing. On the other hand, when the electrode stack 140 has a separator as the separator 130, the electrode stack 140 and the electrolyte (not shown) are sealed in the outer casing.
[0111] The first electrode 110 includes an electrode mixture layer 111 and a porous metal substrate 112, wherein the entirety of the porous metal substrate 112 including the end portion on the electrode mixture layer 111 side is buried in the surface portion of the electrode mixture layer 111. That is, the entirety of the porous metal substrate 112 is equivalent to the region where the electrode mixture layer and the porous metal substrate coexist, i.e., the surface portion of the electrode mixture layer. Furthermore, in the first electrode 110, the end portion ( Figure 2 It should be noted that the dotted line in the first electrode 110 represents the boundary between the region in the electrode mixture layer 111 where the porous metal substrate does not coexist and the region where the electrode mixture layer and the porous metal substrate coexist, which is equivalent to the end of the porous metal substrate 112 on the electrode mixture layer 111 side.
[0112] The second electrode 120 includes an electrode mixture layer 121 and a porous metal substrate 122, wherein the entirety of the porous metal substrate 122 including the end portion on the electrode mixture layer 121 side is buried in the surface portion of the electrode mixture layer 121. That is, the entirety of the porous metal substrate 122 is equivalent to the region where the electrode mixture layer and the porous metal substrate coexist, i.e., the surface portion of the electrode mixture layer. Furthermore, in the second electrode 120, the end portion ( Figure 2 It should be noted that the dotted line in the second electrode 120 represents the boundary between the region in the electrode mixture layer 121 where the porous metal substrate does not coexist and the region where the electrode mixture layer and the porous metal substrate coexist, which is equivalent to the end of the porous metal substrate 122 on the electrode mixture layer 121 side.
[0113] Figure 2 In the electrochemical element 100 shown, the metal outer can 150 forms a conductive path on the first electrode 110 side, and the end of the porous metal substrate 112 exposed on the surface of the first electrode 110 is in contact with the inner surface of the outer can 150, so that the first electrode 110 and the outer can 150 (the conductive path formed by the outer can 150) are connected. In addition, the outer surface of the outer can 150 serves as an external terminal for electrically connecting the electrochemical element to an external device.
[0114] In addition, Figure 2 In the electrochemical element 100 shown, the metal sealing can 160 forms a conductive path on the second electrode 120 side, and the end of the porous metal substrate 122 exposed on the surface of the second electrode 120 contacts the inner surface of the sealing can 160, so that the second electrode 120 and the sealing can 160 (the conductive path formed by the sealing can 160) are connected. In addition, the outer surface of the sealing can 160 serves as an external terminal for electrically connecting the electrochemical element to an external device.
[0115] The outer casing of the electrochemical device is used, for example, Figure 2 The outer casing shown is composed of a case having an outer can and a sealing can. That is, the electrochemical element having such a case as an outer casing has a coin shape (button shape).
[0116] When the outer package of the electrochemical element is a casing having an outer can and a sealing can, Figure 2 As shown, the case in which the outer can and the sealing can are fastened and sealed via a gasket can be exemplified, and the case in which the outer can and the sealing can are bonded with a resin can also be exemplified.
[0117] The outer can and the sealing can can be made of stainless steel or the like. In addition, in addition to polypropylene, nylon, etc., the raw material of the gasket can also be used. When heat resistance is required in relation to the use of the electrochemical element, fluororesins such as tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), polyphenylene sulfide (PPS), polyetheretherketone (PEEK) and other heat-resistant resins with a melting point exceeding 240°C can also be used. In addition, when the electrochemical element is used for applications requiring heat resistance, its seal can also be sealed airtightly with glass.
[0118] It should be noted that the outer casing of the electrochemical element is not limited to an outer casing having an outer can and a sealing can, as long as it has a conductive path extending from the inside to the outside of the outer casing, so that the porous metal substrate on the electrode surface of the electrode stack is in contact with the conductive path and the electrode is electrically connected to the conductive path. For example, a ceramic shell or a shell in which a conductive path composed of a metal such as gold, platinum, silver, palladium, copper, nickel, cobalt or an alloy thereof is arranged in a manner penetrating the constituent material can be used as the outer casing of the electrochemical element.
[0119] The shape of the outer casing of the electrochemical device in plan view may be circular or may be a polygon such as a quadrilateral (square, rectangle).
[0120] In the case of an electrochemical element having an electrode stack with a diaphragm as a separator, an electrolyte is used as described above. The electrolyte generally uses a liquid electrolyte (non-aqueous electrolyte or aqueous electrolyte) having a non-aqueous solvent or an aqueous solvent. Moreover, as the non-aqueous electrolyte, a non-aqueous electrolyte in which an electrolyte salt such as a lithium salt is dissolved in an organic solvent is used. As the organic solvent, there is no particular limitation, and examples thereof include chain esters such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate; cyclic esters with high dielectric constants such as ethylene carbonate, propylene carbonate, butylene carbonate, and vinylene carbonate; mixed solvents of chain esters and cyclic esters, etc., and mixed solvents of chain esters as the main solvent and cyclic esters are particularly suitable.
[0121] As the electrolyte salt dissolved in the organic solvent when preparing the non-aqueous electrolyte, for example, when the electrochemical element is a battery or a lithium ion capacitor, LiPF6, LiBF4, LiAsF6, LiSbF6, LiCF3SO3, LiC4F9SO3, LiCF3CO2, Li2C2F4(SO3)2, LiC n F 2n+1 SO3 (n ≥ 2), LiN (RfSO2) (Rf'SO2), LiC (RfSO2) 3, LiN (RfSO2) 2 [wherein Rf and Rf' are fluoroalkyl groups], etc., or a mixture of two or more thereof. In addition, when the electrochemical element is a double-layer capacitor, the electrolyte salt of the non-aqueous electrolyte solution uses (C2H5) 4NBF4, (C2H5) 4PBF4, etc.
[0122] The concentration of the electrolyte salt in the electrolytic solution is not particularly limited, but is preferably 0.3 mol / l or more, more preferably 0.4 mol / l or more, and is preferably 1.7 mol / l or less, more preferably 1.5 mol / l or less.
[0123] As the aqueous electrolyte, an alkaline aqueous solution (alkaline electrolyte) composed of an aqueous solution of an alkali metal hydroxide such as potassium hydroxide, sodium hydroxide, or lithium hydroxide, an aqueous solution having a pH in the range of 3 to 12, or the like is used.
[0124] The concentration of the hydroxide of the alkali metal in the alkaline electrolyte can be, for example, 25 to 40% by mass.
[0125] In addition, examples of aqueous solutions having a pH in the range of from 3 to 12 include chlorides such as sodium chloride, potassium chloride, magnesium chloride, calcium chloride, ammonium chloride, and zinc chloride; hydroxides of alkali metals and alkaline earth metals (sodium hydroxide, potassium hydroxide, magnesium hydroxide, etc.), acetates (sodium acetate, potassium acetate, magnesium acetate, etc.), nitrates (sodium nitrate, potassium nitrate, magnesium nitrate, etc.), sulfates (sodium sulfate, potassium sulfate, magnesium sulfate, etc.), phosphates (sodium phosphate, potassium phosphate, magnesium phosphate, etc.), borates (sodium borate, potassium borate, magnesium borate, etc.), citrates (sodium citrate, potassium citrate, magnesium citrate, etc.), glutamates (sodium glutamate, potassium glutamate, magnesium glutamate, etc.); alkali metal bicarbonates (sodium bicarbonate, potassium bicarbonate, etc.); alkali metal percarbonates (sodium percarbonate, potassium percarbonate, etc.); halogen-containing compounds such as fluorides; and solutions obtained by dissolving one or more of electrolyte salts such as polycarboxylic acids in water.
[0126] The electrolyte of the electrochemical element may be a gel electrolyte obtained by gelling the above-mentioned electrolytic solution with a gelling agent composed of a polymer or the like.
[0127] Example
[0128] Hereinafter, the present invention will be described in detail based on examples. However, the following examples do not limit the present invention.
[0129] (Example 1)
[0130] The average particle size of lithium titanate (Li4Ti5O 12 , negative electrode active material), a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm and graphene (conductive aid) are mixed in a mass ratio of 50:41:9 to prepare a negative electrode mixture.
[0131] In addition, LiCoO2 (positive electrode active material) with an average particle size of 5 μm and a coating layer of LiNbO3 formed on the surface, a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm, and graphene are mixed in a mass ratio of 65:30.7:4.3 to prepare a positive electrode mixture.
[0132] Next, a powder of a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm was placed in a powder molding mold, and a press was used to preform at a surface pressure of 70 MPa to form a preformed layer of the solid electrolyte layer. Furthermore, the negative electrode mixture was arranged on the upper surface of the preformed layer of the solid electrolyte layer, and preformed at a surface pressure of 50 MPa, and a preformed layer of the negative electrode was further formed on the preformed layer of the solid electrolyte layer.
[0133] Next, a material obtained by cutting a nickel foamed porous metal body (nickel "Celmet" (registered trademark)) made of Sumitomo Electric Industries, Ltd. into a material with a diameter of 7.25 mm (thickness: 1.2 mm, porosity: 98%) is placed on the preformed layer of the negative electrode formed on the preformed layer of the solid electrolyte layer, and pressure molding is performed at a surface pressure of 300 MPa to form an integrated product of the solid electrolyte layer and the negative electrode.
[0134] By the pressure molding, the foamed porous metal body is compressed and buried in the negative electrode mixture in the preformed layer of the negative electrode (negative electrode mixture), thereby obtaining a negative electrode in which the porous metal substrate is buried in the surface layer of the negative electrode mixture layer.
[0135] Furthermore, after turning the mold upside down, the positive electrode mixture is arranged on the upper surface of the solid electrolyte layer in the mold (the opposite side of the surface having the negative electrode), and pre-molded at a surface pressure of 50 MPa to form a pre-molded positive electrode layer on the solid electrolyte layer.
[0136] Next, a nickel-made foamed metal porous body cut from the same foamed metal porous body used in the negative electrode was placed on the preformed layer of the positive electrode formed on the solid electrolyte layer and press-formed at a surface pressure of 1400 MPa to obtain an electrode stack.
[0137] On the positive electrode side, similarly to the negative electrode, a positive electrode can be obtained in which a porous metal substrate is buried in the surface layer of the positive electrode mixture layer.
[0138] In the obtained electrode stack, the thickness of the negative electrode mixture layer of the negative electrode, the thickness of the porous metal substrate, and the thickness of the portion of the porous metal substrate buried in the negative electrode mixture layer were 1400 μm, 60 μm (5% of the thickness of the porous metal substrate before being used for the negative electrode), and 60 μm (100% of the total thickness of the porous metal substrate). In addition, the area ratio of the portion of the negative electrode mixture exposed on the surface of the negative electrode was 7%.
[0139] In addition, in the obtained electrode stack, the thickness of the positive electrode mixture layer of the positive electrode, the thickness of the porous metal substrate, and the thickness of the portion of the porous metal substrate buried in the positive electrode mixture layer were 800 μm, 60 μm (5% of the thickness of the porous metal substrate before being used for the positive electrode), and 60 μm (100% of the overall thickness of the porous metal substrate). In addition, the area ratio of the portion of the positive electrode mixture exposed on the surface of the positive electrode was 7%.
[0140] Comparative Example 1
[0141] An electrode laminate was produced in the same manner as in Example 1 except that the porous metal substrate was not provided at the positive electrode and the negative electrode.
[0142] The electrode stacks of Example 1 and Comparative Example 1 were subjected to impedance measurement by the following method.
[0143] First, using the electrode stacks of Example 1 and Comparative Example 1, coin-shaped all-solid-state batteries were produced according to the following procedures.
[0144] Two flexible graphite sheets "PERMA-FOIL (product name)" (thickness: 0.1 mm, apparent density: 1.1 g / cm) manufactured by Toyo Tanso Co., Ltd. were prepared. 3 ) was punched into a material of the same size as the above-mentioned molded body, one of which was placed on the inner bottom surface of a stainless steel sealing can in which a polyphenylene sulfide annular gasket was embedded, and the electrode stack of Example 1 or Comparative Example 1 was placed thereon in such a way that the negative electrode was on the graphite sheet side. Furthermore, the remaining one graphite sheet was placed on the positive electrode of the electrode stack, and after covering with a stainless steel outer can, the open end of the outer can was tightened inward to seal, thereby manufacturing a coin-shaped all-solid-state battery.
[0145] The coin-shaped all-solid-state battery was charged at a constant current of 4 mA until the voltage reached 2.6 V, then charged at a constant voltage of 2.6 V until the current reached 0.05 mA, and then discharged at a constant current of 0.01 mA until the voltage reached 1.0 V. Next, the battery was charged at a current of 1 mA to adjust the SOC to 10%. Each electrode stack was then taken out from the coin-shaped all-solid-state battery, and the impedance was measured as follows.
[0146] The electrode stack of Example 1 was sandwiched between two SUS plates (SUS304 plates) at both ends, and the AC impedance at 1 kHz was measured with an applied voltage of 10 mV while applying a load of 0.02 N in the thickness direction.
[0147] In addition, about the electrode laminate of Comparative Example 1, impedance measurement was performed under the following three conditions.
[0148] (1) The impedance of the electrode laminate was measured under the same conditions as those of Example 1 except that the load applied in the thickness direction was changed to 2 N. This was referred to as Comparative Example 1-1.
[0149] (2) Flexible graphite sheets “PERMA-FOIL (product name)” (thickness: 0.1 mm, apparent density: 1.1 g / cm) manufactured by Toyo Tanso Co., Ltd. were placed between the positive electrode, the negative electrode and the SUS plate. 3 ) were measured, and the impedance was measured under the same conditions as those of the electrode laminate of Comparative Example 1-1. This was referred to as Comparative Example 1-2.
[0150] (3) Impedance was measured under the same conditions as for the electrode stack of Comparative Example 1-1, except that the same foamed metal porous body as that used in the preparation of the electrode stack of Example 1 was arranged between the positive electrode, the negative electrode and the SUS plate, respectively. This was referred to as Comparative Example 1-3.
[0151] Table 1 shows the above measurement results.
[0152] [Table 1]
[0153]
[0154] As shown in Table 1, the electrode stack of Example 1 having an electrode in which the porous metal substrate is embedded in the surface portion of the electrode mixture layer and the porous metal substrate is integrated with the electrode mixture layer and the end of the porous metal substrate of the electrode is exposed on the surface, even if the load applied in the thickness direction is reduced, the impedance is low. That is, even if the SUS plate is not pressed strongly on the electrode stack, a good conductive connection can be achieved between the electrode and the SUS plate. It can be seen from this that if it is the electrode stack of Example 1, an electrochemical element with low internal resistance and excellent characteristics can be formed.
[0155] In contrast, for the electrode stack of Comparison Example 1 having an electrode without using a porous metal substrate, in any of Comparison Example 1-1 which does not use a current collector, and Comparison Examples 1-2 and 1-3 in which a graphite sheet functioning as a current collector and a foamed metal porous body are arranged on the electrode surface but are not integrated with the electrode, even if the load applied in the thickness direction is increased and the SUS plate is pressed strongly toward the electrode stack side, the impedance becomes higher than that of the electrode stack of Example 1.
[0156] The present invention can also be implemented as a mode other than the above without departing from the scope of its purport. The embodiment disclosed in this application is an example, and the present invention is not limited to these embodiments. For the scope of the present invention, compared with the description of the above specification, the description in the attached claims is given priority for interpretation, and all changes within the scope equivalent to the claims are included in the claims.
[0157] Industrial Applicability
[0158] The electrochemical device of the present invention can be used in the same applications as conventionally known electrochemical devices. In addition, the electrode laminate of the present invention can constitute the electrochemical device of the present invention.
[0159] Description of Reference Numerals
[0160] 10: Porous metal substrate,
[0161] 11: Electrode mixture,
[0162] 100: electrochemical components,
[0163] 110: first electrode,
[0164] 111: electrode mixture layer,
[0165] 112: Porous metal substrate,
[0166] 120: second electrode,
[0167] 121: electrode mixture layer,
[0168] 122: Porous metal substrate,
[0169] 130: Isolation layer,
[0170] 140: electrode stack,
[0171] 150: outer can,
[0172] 160: Sealing jar,
[0173] 170: Gasket.
Claims
1. An electrode stack, characterized in that: An electrode stack having a first electrode, a second electrode and a separator interposed therebetween, At least one of the first electrode and the second electrode comprises an electrode mixture layer and a sheet-like porous metal substrate. At least a portion of the end portion of the porous metal substrate including the electrode mixture layer side is embedded in the surface layer portion of the electrode mixture layer to be integrated with the electrode mixture layer. The other end of the porous metal substrate is exposed on the surface of the electrode.
2. The electrode stack according to claim 1, wherein The porous metal substrate is a compressed foamed metal porous body.
3. The electrode stack according to claim 1, wherein The isolation layer is a solid electrolyte layer.
4. The electrode stack according to any one of claims 1 to 3, wherein The thickness of the porous metal substrate is 30% or less of the thickness of the electrode mixture layer.
5. A method for producing an electrode stack, which is a method for producing the electrode stack according to claim 1, characterized in that: have: In the first step, the electrode mixture is put into a mold and pressurized for preforming; A second step of placing a sheet-shaped porous metal substrate on the electrode mixture preformed in the first step; as well as In the third step, the porous metal substrate is pressurized and compressed toward the electrode mixture, so that at least a portion of the end portion of the porous metal substrate including the electrode mixture side is buried in the electrode mixture, thereby forming an electrode mixture layer integrated with the porous metal substrate.
6. The method for producing an electrode stack according to claim 5, wherein: A foamed porous metal body is used as the porous metal substrate.
7. The method for producing an electrode stack according to claim 5, wherein: The separation layer of the electrode stack is a solid electrolyte layer, Prior to the first step, there is a preparatory step of placing a solid electrolyte into a mold and pressurizing it for preforming. The first step is performed by placing the electrode mixture on the preformed solid electrolyte.
8. The method for producing an electrode stack according to any one of claims 5 to 7, wherein: In the third step, the thickness of the porous metal substrate is set to be 30% or less of the thickness before compression.
9. An electrochemical element, characterized in that: The electrode stack according to claim 1, comprising an outer casing and an interior sealed in the outer casing, The outer casing has a conductive path extending from the inside to the outside, The porous metal substrate on the electrode surface of the electrode stack is brought into contact with the conductive path, so that the electrode and the conductive path are electrically connected.
10. The electrochemical element according to claim 9, wherein The porous metal substrate is a compressed foamed metal porous body.
11. The electrochemical element according to claim 9, wherein The isolation layer is a solid electrolyte layer.
12. The electrochemical device according to any one of claims 9 to 11, wherein The thickness of the porous metal substrate is 30% or less of the thickness of the electrode mixture layer.
Citation Information
Patent Citations
All-solid lithium battery
JP1998247516A
Flat solid-state battery and method for manufacturing same
WO2020066323A1
Halide solid electrolyte material and battery using same
WO2020070955A1
Halide solid electrolyte material and battery using same
WO2020070958A1